The Influence of Digital Tax Education and Deterrence Perception on Pre-Compliance Intentions: A Study of Generation Z University Students - Alfian, Rizky; Raniah, Putri Syahla; Irawan, Tasya Meydina; Simangunsong, Elsya Yunita; Linawati (Sinergi International Journal of Economics, 2025)
This study examines the effect of digital tax education and perceived tax sanctions on the pre-compliance intention of Generation Z university students. A quantitative research design was employed, unlike previous studies focusing on registered taxpayers, this research highlights the formative stage of future taxpayers. Data were obtained from online questionnaires administered to 100 Generation Z students at Pamulang University. The results reveal that digital tax education has a positive and significant impact on pre-compliance intentions, indicating that higher quality and more accessible digital tax education enhances individuals’ willingness to fulfill their tax obligations. Furthermore, perceptions of tax sanctions also demonstrate a positive and significant effect, suggesting that the belief in strict and consistently enforced sanctions increases compliance intentions. Overall, the study concludes that effective digital-based tax education combined with strong sanction perceptions plays a strategic role in shaping the future pre-compliance intentions of Generation Z. These findings offer practical insights for tax authorities in developing educational and enforcement strategies suited to the digital era.